2018
DOI: 10.1371/journal.pone.0208851
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum monoclonal antibodies against chikungunya virus structural proteins: Promising candidates for antibody-based rapid diagnostic test development

Abstract: In response to the aggressive global spread of the mosquito-borne chikungunya virus (CHIKV), an accurate and accessible diagnostic tool is of high importance. CHIKV, an arthritogenic alphavirus, comprises three genotypes: East/Central/South African (ECSA), West African (WA), and Asian. A previous rapid immunochromatographic (IC) test detecting CHIKV E1 protein showed promising performance for detection of the ECSA genotype. Unfortunately, this kit exhibited lower capacity for detection of the Asian genotype, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…In cells transduced with ChAdOx1 sCHIKV ∆C we also detected bands at approximately 55 kDa in supernatants (Figure 3c, lane 5,6,7), but no bands of 50 kDa or 18 kDa were found in the concentrated supernatant nor in the cell extracts. Therefore, it is suggested that the 35 kDa or 18 kDa band may represent the capsid protein, as previously demonstrated [38], which are not present in ChAdOx1 sCHIKV ∆C-transduced cells. As a positive control, we used a commercially available CHIKV E1 protein (Figure 3c, lane 9); therefore, it is suggested that the 55 kDa band detected in our blots is E1 protein.…”
Section: Resultsmentioning
confidence: 79%
“…In cells transduced with ChAdOx1 sCHIKV ∆C we also detected bands at approximately 55 kDa in supernatants (Figure 3c, lane 5,6,7), but no bands of 50 kDa or 18 kDa were found in the concentrated supernatant nor in the cell extracts. Therefore, it is suggested that the 35 kDa or 18 kDa band may represent the capsid protein, as previously demonstrated [38], which are not present in ChAdOx1 sCHIKV ∆C-transduced cells. As a positive control, we used a commercially available CHIKV E1 protein (Figure 3c, lane 9); therefore, it is suggested that the 55 kDa band detected in our blots is E1 protein.…”
Section: Resultsmentioning
confidence: 79%
“…Hence, the closer alphaviruses are phylogenetically, the more cross-reactivity exists [194]. In response, considerable effort is made on developing technologies to avoid cross-reactivity both in direct [271,277] and indirect diagnosis [194,278].…”
Section: Discussionmentioning
confidence: 99%
“…The reactivity was reported against East/Central/South African (ECSA), West African, and Asian genotypes and MAbs also possessed no cross reactivity. Moreover, these MAbs are being used to detect E1 glycoprotein for detection of CHIKV infection via rapid immunochromatographic (IC) detection kits and worked well for all three CHIKV genotypes and possess great value in clinical diagnosis [80].…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%
“…MAb targeting the E1 glycoprotein of CHIKV i.e. CK47 restricted the viral dissemination via inhibiting its budding during replication [80]. Fox et al reported the importance of interaction between Fc region of therapeutic MAbs and Fcγ receptors (FcγR) of effector cells such as monocytes during CHIKV infection.…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%